Stereotypes and Values Related to Gender in Business - Monika RÓŻYCKA; Ireneusz MICIUŁA (Communications of International Proceedings, 2020)
The aim of this article is to analyze and discuss the socio-cultural barriers related to entrepreneurship. At the same time, an attempt was made to show the connections between gender stereotypes and values. The article distinguishes female values against male values and determines their significance for functioning in the business world.
Keywords: Stereotypes; Values; The Concept of Female Values in Business; Entrepreneurship; Economy.